Who are you? Online practices of self-representation of black gay men at Rhodes University on the geosocial networking application Grindr - Olivier, Jason Eben (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
The study investigates how young black gay men at Rhodes University use technology to explore their sexual identity and focuses specifically on their self-representation choices. Incorporating qualitative semi-structured interviews and a walkthrough of Grindr, the research asked participants to share their experiences of using Grindr, a geo-social networking application, and how their self-representation practices on the site contributed to their conception of what it means to be a young black gay man online. Using a thematic analysis of the data collected from five self-identified black gay Rhodes University students, findings indicate that self-representation choices of black gay men on Grindr become a complex experience influenced by overt sexist and racist micro-aggressions in an environment where masculinities operate in a hierarchy of desire, preference, and attractiveness with race operating as an important signifier of these even in a post-Apartheid South Africa that is celebrated for its world-class Constitution.
Keywords: Grindr (Computer program); Gay men, Black -- South Africa -- Makhanda; Gay men Identity; Internet and gay men -- South Africa -- Makhanda; Social media and college students -- South Africa -- Makhanda; Masculinity -- South Africa -- Makhanda; Racism in the sexual minority community -- South Africa -- Makhanda; Sexism -- South Africa -- Makhanda; Rhodes University